PERBANDINGAN STOCK MARKET CRASH 1987 :' DAN STOCK MARKET CRASH 1997 - Yovita Vivianty Indridewi Atmadjaja (Center for Economic Studies Universitas Katolik Parahyangan, 1999)
Stock market crash refers to the condition, which is marked with the large dropping of stock Market price index. Historically, stock market crash has happened three times, namely in 1929, 1987 and 1997. This paper will discuss the causes of 1987's and 1997's stock market Crash and the similarities and the differences between 1987's and 1997's stock market crash. The structure of the paper is as follows. The paper starts with the introduction. The second Section briefly explains the causes of the 1987's stock market crash. The third section Discusses the major cause of the 1997's stock market crash. The fourth and the fifth sections Contain the similarities and the differences between the event leading up the 1987 crash and The stock market crash in 1997. And the last section is the conclusion.